2020
DOI: 10.3390/ijms21218139
|View full text |Cite
|
Sign up to set email alerts
|

The Distinct Function and Localization of METTL3/METTL14 and METTL16 Enzymes in Cardiomyocytes

Abstract: It has become evident that epitranscriptome events, mediated by specific enzymes, regulate gene expression and, subsequently, cell differentiation processes. We show that methyltransferase-like proteins METTL3/METTL14 and N6-adenosine methylation (m6A) in RNAs are homogeneously distributed in embryonic hearts, and histone deacetylase (HDAC) inhibitors valproic acid and Trichostatin A (TSA) up-regulate METTL3/METTL14 proteins. The levels of METTL3 in mouse adult hearts, isolated from male and female animals, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…We have recently shown distinctions between METTL3/METTL14 and METTL16 proteins in embryonic stem cells (ESCs) experimentally stimulated into cardiomyocytes. We have also observed that the nuclear pools and nuclear distribution of METTL3/METTL14 proteins in mouse ESCs were different from those studied in METTL16 [ 33 ]. Ruszkowska et al [ 11 ] also showed that the molecular structure of METTL16 is different from the structure of METTL3 and METTL14 proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown distinctions between METTL3/METTL14 and METTL16 proteins in embryonic stem cells (ESCs) experimentally stimulated into cardiomyocytes. We have also observed that the nuclear pools and nuclear distribution of METTL3/METTL14 proteins in mouse ESCs were different from those studied in METTL16 [ 33 ]. Ruszkowska et al [ 11 ] also showed that the molecular structure of METTL16 is different from the structure of METTL3 and METTL14 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in mouse 16-cell embryos, characterized by Mettl16 depletion, it was found that the mRNA level was reduced. This observation indicates that METTL16 plays a role in early development and, therefore, cell differentiation [ 17 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“… 160 The expression of METTL3 and METTL14, as well as the abundance of m 6 A in RNAs, are evenly distributed in embryonic hearts, and their expression is increased by the histone deacetylase inhibitors valproic acid and Trichostatin A. 159 …”
Section: N 6 -Methyladenosine and A-to-i Modificat...mentioning
confidence: 99%
“…The transcriptome data also reflects the importance of epigenetic changes elicited by MPP+ in both CV and LDH-A/B DKOs, evidenced by the sheer number of downregulated histone cluster transcripts as well as the massive bidirectional DEGs in non-protein coding microRNA and long-intergenic transcripts. MPP+ also evoked changes in a number of METTL transcripts, which are believed to contribute to nucleoside modifications in diverse types of RNA and DNA (86,87), however very little is known on these particular epigenetic modifications.…”
Section: Table II David Functional Annotation Pathway Analysis Of Up-regulated Degs Caused By Mpp+ When Comparing Controls Vs Controls + mentioning
confidence: 99%